First-Principles Calculations of Plasmon-Induced Hot Carrier Properties of μ-Ag3Al - Zihan Zhao; Hai Ren; Yucheng Wang; Xiangchao Ma; Jiali Jiang; Linfang Wei; Delian Liu (Nanomaterials)
Non-radiative decay of surface plasmon (SP) offers a novel paradigm for efficient conversion of photons into carriers. However, the narrow bandwidth of SP has been a significant obstacle to the widespread applications. Previously, research and applications mainly focused on noble metals such as Au, Ag, and Cu. In this article, we report an Ag-Al alloy material, μ-Ag3Al, in which the surface plasmon operating bandwidth is 1.7 times that of Ag and hot carrier transport properties are comparable with those of AuAl. The results show that μ-Ag3Al allows efficient direct interband electronic transitions from ultraviolet (UV) to near infrared range. Spherical nanoparticles of μ-Ag3Al exhibit the localized surface plasmon resonance (LSPR) effect in the ultraviolet region. Its surface plasmon polariton (SPP) shows strong non-radiative decay at 3.36 eV, which is favorable for the generation of high-energy hot carriers. In addition, the penetration depth of SPP in μ-Ag3Al remains high across the UV to the near-infrared range. Moreover, the transport properties of hot carriers in μ-Ag3Al are comparable with those in Al, borophene and Au-Al intermetallic compounds. These properties can provide guidance for the design of plasmon-based photodetectors, solar cells, and photocatalytic reactors.